Joint association of physical activity and sleep duration with all-cause and cause-specific mortality: A prospective study of 153,866 Mexican adults - da Silva, Weder Alves; Christofaro, Diego [UNESP]; Del Val Martín, Pablo; Marques, Adilson; Peralta, Miguel; Cristi-Montero, Carlos; Rezende, Leandro F M; Chiappa, Gaspar; Ferrari, Gerson (Elsevier, 2025)
OBJECTIVE: This study investigated the joint association of physical activity (weekly frequency and duration) and sleep duration with all-cause and cause-specific mortality. METHODS: We conducted a prospective cohort study of 153,866 participants from the Mexico City Prospective Study. Cox proportional hazards regression was used to estimate the joint associations of frequency (none, < 1, 1-2, and ≥ 3 times/week) and session duration (none, < 30, 30-60, and ≥ 60 min/day) of physical activity and sleep duration (recommended: 7-9 h/day; below/above recommended: <7 or > 9 h/day) with the risk of all-cause and cause-specific mortality (cardiovascular disease, cancer, and respiratory diseases). RESULTS: Over 15.6 years of follow-up, higher risks of all-cause, cardiovascular diseases, and cancer mortality were observed among participants with: no physical activity and recommended sleep duration; < 1 time/week of physical activity and below/above recommended sleep; and no physical activity and below/above recommended sleep (compared to higher physical activity and recommended sleep duration. Similar positive associations were observed when considering physical activity duration. The highest risks of all-cause, cardiovascular disease, and cancer mortality were found among participants with no physical activity (duration) and below/above recommended sleep duration. CONCLUSIONS: Our findings suggest that low levels of physical activity and non-recommended sleep durations jointly increase the risk of all-cause and cause-specific mortality.